Proposed marketing strategy to increase the revenue of a management consulting firms - Arauna, Radita Sonixtus; Aditya Wibowo , Satya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The lack of execution guidelines is not the only problem faced by the consulting firms. They have other challenges to consult towards broad range of different segment and target, which each and every segment have their own characteristic, challenges, and difficulties. In its 4 years of company establishment, NAS realized that as any other newly developed company, it probably did not have the strong base for sustainable business. In this study, the author uses the AFI framework (Analysis, Formulation, and Implementation) in determining the right strategy to increase the competitiveness of NAS in the market. Primary data earned from quantitative research by spreading questionnaire to respondents and qualitative research by conducting depth interview for respondents to gain deeper insight as well as interview with an internal organization of NAS. Secondary data earned from articles, journals, and company data. The result shows that although NAS revenue has continued to increase since the first of its establishment, after analyzing one of the revenue clusters, it turns out that the largest NAS revenue does not come from consulting activities which are the main service of NAS itself, while market research which is a supporting service from NAS occupies the first position by donating 37 persen average income in the period 2018-2021. An even more surprising figure is that 34 persen of the average NAS revenue comes from service provider activities that are not part of the NAS core services and only acts as a single, unsustainable service activity.